Are reasons for care‐giving related to carers' care‐related quality of life and strain? Evidence from a survey of carers in England. (31st July 2018) - Rand, Stacey; Malley, Juliette; Forder, Julien
Abstract: In England, choice and control is promoted for service users in relation to social care services. Increased choice and control has also been promoted for unpaid carers, although this is still relatively underdeveloped. There is limited recognition of carers' choice in terms of the decision of whether to provide care. Alongside the promotion of choice and control, there has also been a focus on quality of life as an outcome of social care for care‐recipients and their carers. Although it is known that carer choice (in terms of the decision of whether or not to provide care) is related to increased burden and poorer psychological health, there is limited evidence of the relationship between reasons for caring and care‐related quality of life (CRQoL) and subjective strain in England. In this study, 387 carers were surveyed across 22 English local authorities between June 2013 and March 2014. Multiple regression analysis explored the relationship between carer‐reported reasons for caring and CRQoL and strain, whilst controlling for individual characteristics (e.g. age). Reasons for caring were important predictors of CRQoL and strain. Where people were carers because social services suggested it or the care‐recipient would not want help from anyone else, this was related to lower CRQoL. By contrast, where carers took on care‐giving because they had time to care, this was significantly associated with better CRQoL. Carers reported greater strain where they provided care because it was expected of them. These findings are relevant to policy and practice because they indicate that, while social care systems rely on carers, the limiting of carers' choice of whether to provide care is related to worse outcomes. Increased awareness of this relationship would be beneficial in developing policy and practice that improves the QoL of care‐recipients and also their carers.